Type-I IFN Signaling Suppresses an Excessive IFN-γ Response and Thus Prevents Lung Damage and Chronic Inflammation During Pneumocystis (PC) Clearance in CD4 T Cell-Competent Mice - Meissner, Nicole (American Society for Investigative Pathology, 2010)
Immune-reconstitution after highly active antiretroviral therapy (HAART) is often incomplete, and some HIV-infected individuals fail to regenerate type-I interferon (IFN)–producing pDCs. We recently demonstrated that during Pneumocystis (PC) infection in CD4 T cell–competent mice the absence of type-I IFN signaling results in chronic pulmonary inflammation and fibrosis despite clearance. Because the mechanisms involved are poorly understood, we further characterized the role of type-I IFN signaling in immune responses to PC. We show that type-I IFN signaling around day 7 postinfection is critical to the outcome of inflammation. Microarray analysis of pulmonary CD11c(+) cells revealed that at day 7 post infection, wild-type cells up-regulated type-I IFN–responsive genes as well as SOCS1, which is a critical negative-regulator of type-I IFN and IFN-γ signaling. This was associated with an eosinophilic lung inflammation, PC clearance, and complete restitution. However, pulmonary CD11c(+) cells from IFNAR(−/−) mice demonstrated increased tumor necrosis factor (TNF)-α production and lacked SOCS1-induction at day 7. This was followed by a transient lymphocytic and IFN-γ response before switching to a chronic eosinophilic inflammation of the lung. Early neutralization of TNF-α did not prevent chronic inflammation in IFNAR(−/−) mice, but treatment with an anti–IFN-γ antibody did. We propose that during PC lung infection type-I IFNs induce SOCS1-associated regulatory mechanisms, which prevent excessive IFN-γ–mediated responses that cause chronic lung damage. Therefore, partial immune-reconstitution in AIDS, attributable to reduced type-I IFN actions, might disrupt regulatory aspects of inflammation, causing unexplained chronic pulmonary complications as seen in some patients during HAART.